Tính: \(a)\sqrt {16} ;b)\sqrt {81} ;c)\sqrt {{{2021}^2}} \)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\sqrt{24+16\sqrt{2}}-\sqrt{24-16\sqrt{2}}=\sqrt{\left(4+\sqrt{8}\right)^2}-\sqrt{\left(4-\sqrt{8}\right)^2}=\left|4+\sqrt{8}\right|-\left|4-\sqrt{8}\right|=4+\sqrt{8}-4+\sqrt{8}=4\sqrt{2}\)
\(\sqrt[3]{16-8\sqrt{5}}\)=\(\sqrt[3]{1-3\sqrt{5}+15-5\sqrt{5}}\)=\(\sqrt[3]{1-3\sqrt{5}+3\left(\sqrt{5}\right)^2-\left(\sqrt{5}\right)^3}\)=\(\sqrt[3]{\left(1-\sqrt{5}\right)^3}\)=\(1-\sqrt{5}\)
làm tương tự: \(\sqrt[3]{16+8\sqrt{5}}\)=\(1+\sqrt{5}\)
suy ra: a = 2
a) Pt \(\Leftrightarrow\sqrt{\left(x-2\right)^2}=5\Leftrightarrow\left|x-2\right|=5\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=5\\x-2=-5\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=7\\x=-3\end{matrix}\right.\)
Vậy...
b)Đk: \(x\ge-1\)
Pt \(\Leftrightarrow4\sqrt{x+1}-3\sqrt{x+1}+2\sqrt{x+1}=16-\sqrt{x+1}\)
\(\Leftrightarrow4\sqrt{x+1}=16\)\(\Leftrightarrow x+1=16\)\(\Leftrightarrow x=15\) (tm)
Vậy...
\(A=\dfrac{a^2+\sqrt{a}}{a-\sqrt{a}+1}-\dfrac{2a+\sqrt{a}}{\sqrt{a}}+1\) (a>0)
\(=\dfrac{\sqrt{a}\left(\sqrt{a}+1\right)\left(a-\sqrt{a}+1\right)}{a-\sqrt{a}+1}-\dfrac{\sqrt{a}\left(2\sqrt{a}+1\right)}{\sqrt{a}}+1\)
\(=a+\sqrt{a}-\left(2\sqrt{a}+1\right)+1=a-\sqrt{a}\)
b) \(A=a-\sqrt{a}=a-2.\dfrac{1}{2}\sqrt{a}+\dfrac{1}{4}-\dfrac{1}{4}=\left(\sqrt{a}-\dfrac{1}{2}\right)^2-\dfrac{1}{4}\ge-\dfrac{1}{4}\)
Dấu "=" xảy ra khi \(\sqrt{a}=\dfrac{1}{2}\Leftrightarrow a=\dfrac{1}{4}\left(tmđk\right)\)
Vậy \(A_{min}=-\dfrac{1}{4}\)
a) \(\sqrt{x^2-4x+4}=5\Rightarrow\sqrt{\left(x-2\right)^2}=5\Rightarrow\left|x-2\right|=5\)
\(\Rightarrow\left[{}\begin{matrix}x-2=5\\x-2=-5\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=7\\x=-3\end{matrix}\right.\)
b) \(\sqrt{16x+16}-3\sqrt{x+1}+\sqrt{4x+4}=16-\sqrt{x+1}\)
\(\Rightarrow\sqrt{16\left(x+1\right)}-3\sqrt{x+1}+\sqrt{4\left(x+1\right)}+\sqrt{x+1}=16\)
\(\Rightarrow4\sqrt{x+1}-3\sqrt{x+1}+2\sqrt{x+1}+\sqrt{x+1}=16\)
\(\Rightarrow4\sqrt{x+1}=16\Rightarrow\sqrt{x+1}=4\Rightarrow x=15\)
a) \(A=\dfrac{a^2+\sqrt{a}}{a-\sqrt{a}+1}-\dfrac{2a+\sqrt{a}}{\sqrt{a}}+1\)
\(=\dfrac{\sqrt{a}\left(\sqrt{a}+1\right)\left(a-\sqrt{a}+1\right)}{a-\sqrt{a}+1}-\dfrac{\sqrt{a}\left(2\sqrt{a}+1\right)}{\sqrt{a}}+1\)
\(=a+\sqrt{a}-2\sqrt{a}-1+1=a-\sqrt{a}\)
b) Ta có: \(a-\sqrt{a}=\left(\sqrt{a}\right)^2-2.\sqrt{a}.\dfrac{1}{2}+\left(\dfrac{1}{2}\right)^2-\dfrac{1}{4}\)
\(=\left(\sqrt{a}-\dfrac{1}{2}\right)^2-\dfrac{1}{4}\ge-\dfrac{1}{4}\)
\(\Rightarrow A_{min}=-\dfrac{1}{4}\) khi \(a=\dfrac{1}{4}\)
a)\(\dfrac{3}{4}-\dfrac{5}{2}-\dfrac{3}{5}=\dfrac{15}{20}-\dfrac{50}{20}-\dfrac{12}{20}=-\dfrac{47}{20}\)
b) \(\sqrt{7^2}+\sqrt{\dfrac{25}{16}-\dfrac{3}{2}}=7+\sqrt{\dfrac{1}{16}}=7+\dfrac{1}{4}=\dfrac{29}{4}\)
c) \(\dfrac{1}{2}.\sqrt{100}-\sqrt{\dfrac{1}{16}+\left(\dfrac{1}{3}\right)^0}=\dfrac{1}{2}.10-\sqrt{\dfrac{1}{16}+1}=5-\sqrt{\dfrac{17}{16}}\)
ta có:
\(\left(\sqrt{16-2x+x^2}+\sqrt{9-2x+x^2}\right)\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)=7\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)\)
\(\Leftrightarrow\left(16-2x+x^2-9+2x-x^2\right)=7\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)\)
\(\Leftrightarrow7=7\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)\)
\(\Leftrightarrow\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}=1\)
Ta có:
\(\left(\sqrt{16-2x+x^2}+\sqrt{9-2x+x^2}\right)\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)=7\)
\(\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)\)
\(\Leftrightarrow\left(16-2x+x^2-9+2x-x^2\right)=7\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)\)
\(\Leftrightarrow7=7\left(\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}\right)\)
\(\Leftrightarrow\sqrt{16-2x+x^2}-\sqrt{9-2x+x^2}=1\)
Ủng hộ nha
a) Vì \({4^2} = 16\) nên \(\sqrt {16} = 4\)
b) Vì \({9^2} = 81\) nên \(\sqrt {81} = 9\)
c) Vì 2021 > 0 nên \(\sqrt {{{2021}^2}} = 2021\)